2004
DOI: 10.1001/jama.291.23.2834
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Acne Vulgaris With a Pulsed Dye Laser

Abstract: Context The high prevalence of acne vulgaris and its significant morbidity underscore the need for convenient, low-risk, and efficacious therapy. Treatment with various lasers has been reported to improve acne. Objective To evaluate the clinical efficacy of pulsed dye laser therapy in the treatment of acne. Design, Setting, and Patients Randomized, single-blind, controlled, split-face clinical trial of a volunteer sample of 40 patients aged 13 years or older with facial acne conducted at an academic referral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
137
2
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(147 citation statements)
references
References 17 publications
6
137
2
2
Order By: Relevance
“…Virtually the full spectrum of visible radiation has been used to treat acne [11][12][13][14][15][16][17][18][19][20][21]. Blue wavelengths of visible light have been used to exploit endogenous porphyrins in proprionibacterium acnes bacteria, targeting these bacteria and reducing their numbers [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Virtually the full spectrum of visible radiation has been used to treat acne [11][12][13][14][15][16][17][18][19][20][21]. Blue wavelengths of visible light have been used to exploit endogenous porphyrins in proprionibacterium acnes bacteria, targeting these bacteria and reducing their numbers [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Blue wavelengths of visible light have been used to exploit endogenous porphyrins in proprionibacterium acnes bacteria, targeting these bacteria and reducing their numbers [11,12]. Visible lasers targeting hemoglobin have also been shown to have activity against acne [19][20][21]. Photodynamic therapy, using a variety of visible wavelengths and a number of photosensitizing dyes, has been used to treat acne [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Lasers have been used effectively in treatment of acne vulgaris using Diode and PDL using one or three sessions of laser but there is one study using PDL showed no significant improvement of facial acne using single session [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…While another study also using Diode laser didn't show significant improvement of facial acne [13][14][15].…”
Section: Introductionmentioning
confidence: 90%
“…The presence of P. acnes promotes inflammation through a variety of mechanisms. P. acnes stimulates inflammation by producing pro-inflammatory mediators that diffuse through the follicle wall [3][4][5][6][7][8].…”
Section: The Pathophysiology Of Acne Involves Four Key Mechanisms Of mentioning
confidence: 99%